2010
DOI: 10.1111/j.1365-2591.2010.01760.x
|View full text |Cite
|
Sign up to set email alerts
|

Review of pulp sensibility tests. Part ΙΙ: electric pulp tests and test cavities

Abstract: The electric pulp test (EPT) is one type of pulp sensibility test that can be used as an aid in the diagnosis of the status of the dental pulp. However, like thermal pulp sensibility tests, it does not provide any direct information about the vitality (blood supply) of the pulp or whether the pulp is necrotic. The relevant literature on pulp sensibility tests in the context of endodontics up to January 2009 was reviewed using PubMed and MEDLINE database searches. This search identified articles published betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
69
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 83 publications
(222 reference statements)
1
69
0
4
Order By: Relevance
“…Children and teenagers were excluded from the study because the patient response in this group may be unreliable (1,33). With elderly patients, a decrease in nervous elements, a decrease in pulp volume, and some changes in interstitial tissues may cause false responses (2,34). Extensive restorations and pulp calcification may be considered other limitations in the reliability of sensitivity tests in these patients (35).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Children and teenagers were excluded from the study because the patient response in this group may be unreliable (1,33). With elderly patients, a decrease in nervous elements, a decrease in pulp volume, and some changes in interstitial tissues may cause false responses (2,34). Extensive restorations and pulp calcification may be considered other limitations in the reliability of sensitivity tests in these patients (35).…”
Section: Discussionmentioning
confidence: 98%
“…Some other factors that may influence study results are the sex of the patients, the pathology of the teeth, the health status of the subjects (eg, infection, fever, and so on), the differential diagnosis of vital pulps and necrotic ones, the history of the teeth, and so on (1,2). An important part of this study was to make a specific dental probe for application of pulse oximetry in pulp diagnosis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The EPT can only be used to determine whether or not there is viable tissue in the root canal and cannot be used to determine the degree of pulp disease or vitality [1618]. Furthermore, no studies have demonstrated any utility of the readings or numerical display [19]. On the other hand, pulp vitality tests to analyze the presence of pulp blood flow by laser Doppler flow or pulse oximetry are considered as better methods of gauging pulp health than sensibility tests [14, 20].…”
Section: Discussionmentioning
confidence: 99%
“…Current diagnostic methods help in fair assessment of accurate size and nature of a periapical lesion which determine the treatment and prognosis of the tooth in question [35]. Making the correct pulpal and periapical diagnosis is helpful for treatment and prognosis of the tooth [1].…”
Section: Introductionmentioning
confidence: 99%